Galactic Archaeology: what changes when ages are known?. Issue 67 (17th July 2015) - Chiappini, C.; Anders, F.; Minchev, I.
Abstract : Galactic Archaeology has recently been challenged by the fact that stars observed now in a certain location are not necessarily born there, but could have been kicked out from their birth places by different internal and/or external processes. We have made one of the first attempts to quantify how important stellar mixing could be in the case of our Galaxy, and how much of the original chemodynamical correlations would have been destroyed by such processes. Our unique approach has allowed us to conclude that although stellar mixing does take place in our Galaxy, many of the main relations between chemistry and age suggested by pure chemical evolution models are still generally valid. However, stringent constraints can be obtained only when stellar ages will be known for a large number of field stars. This is certainly one of the goals of Gaia, but in the meantime it has been shown that Asteroseismology can also provide a way to estimate ages of giants, even at large distances from the Sun. Here we present the first results obtained with a sample of CoRoT stars that have APOGEE spectra, in the framework of the CoRoGEE collaboration. The results coming from this still very recent approach ( i.e. asteroseismology of Galactic populations) reveals that we might be on the right track in terms of quantifying radial mixing, but these results also suggest the chemical enrichment of the Galactic disk(s) to have been more complex than previously envisaged. Intriguingly, we find that the use of [α/Fe]-ratios as proxy for age, although generally valid, breaks down for some stars.